Effectiveness of the Functional Movement Screen for assessment of injury risk occurrence in football players - Lyp, M.; Rosinski, M.; Chmielewski, J.; Czarny-Dzialak, M. A.; Osuch, M.; Urbanska, D.; Wójcik, T.; Florek-Luszczki, M.; Stanislawska, I. (Biology of Sport, 2022)
The aim of the study was to determine whether the Functional Movement Screen (FMS) test carried out among young boys practising football training identifies previous injuries. Sixty-five boys aged 12-13 years, who had regularly practised football in an academy for at least 3 years, were recruited and divided into two groups: an injured group (IG), consisting of players who had experienced at least one injury in the past (n + 25, age 12.32 ± 0.48) and a non-injured group (non-IG), a control group, made up of athletes with no injuries to the musculoskeletal system (n = 40, age 12.25 ± 0.49). Seven FMS tests were used to rate the functional fitness level as a part of the FMS tool. Significant differences between the total scores of the FMS tests (p < 0.001, r = 0.54) were documented. Higher scores in the FMS test were observed in the control group (M = 16.58, SD = 2.04) than in the study group (M = 14.20, ± SD = 1.96). The FMS test is an effective diagnostic tool to identify previous injuries among young football players.